The effectiveness of using ID broth in identifying the outer membrane protein of Salmonella typhi - Pestariati, Pestariati; Suhariyadi, Suhariyadi (International Journal of Public Health Science (IJPHS), 2025)
Typhoid fever is an infection that affects the digestive system. It spreads through contaminated food and drinks due to the Salmonella bacteria. One way to develop immunity against Salmonella typhi is by using outer membrane protein (OMP), which activates the cellular immune system. This research aimed to determine the effectiveness of using ID Broth to identify OMP Salmonella typhi. The study was conducted experimentally at the Institute of Tropical Disease from April 2023 to May 2023. For the study, we obtained three samples of Salmonella typhi isolated from East Java, and each sample was replicated three times. We isolated the bacteria and extracted the OMP to measure its levels and perform electrophoresis with SDS-PAGE. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) is a standard protein analysis method. To address sample loading challenges due to stacking gel transparency, an acidic dye was added to improve visibility without affecting gel performance. In this study nutrient agar from MacConkey medium and ID broth were used as variables. We cultured Salmonella typhi and extracted OMP using the sonication technique. We measured protein levels through the nanodrop method. Salmonella typhi from ID broth produced higher protein levels than Salmonella typhi cultured from MacConkey Medium. It affected the identification of OMP using SDS-PAGE. Lower protein levels lead to fewer protein molecules in the same band zone, causing reduced visibility and readability of the protein bands. The ID broth stabilizes the bacteria's condition before being grown on nutrient agar media.